PERAN SEKTOR PARIWISATA DALAM UPAYA MENINGKATKAN PENDAPATAN ASLI DAERAH KABUPATEN TABANAN - AYUK, NI MADE TAMAN; DEWI, I GUSTI AYU META PURMINA; YASMITA, I GUSTI AYU LIA (GANEC SWARA, 2023)
This study aims to determine the influence of the number of tourist visits, hotel occupancy rates, and tourism sector revenue, both partially and simultaneously, on the Local Own-Source Revenue (PAD) of Tabanan Regency for the years 2017 to 2021. The dependent variable in this research is the Local Own-Source Revenue (PAD) of Tabanan Regency, while the independent variables are the Number of Tourist Visits, Hotel Occupancy Rates, and Tourism Sector Revenue. To examine the influence of the independent variables on the dependent variable, the researcher conducted time series regression testing.The results of hypothesis testing, partially, are as follows: 1) The Number of Tourist Visits does not have a partial influence on the Local Own-Source Revenue of Tabanan Regency, 2) The Hotel Occupancy Rates do not have a partial influence on the Local Own-Source Revenue of Tabanan Regency, 3) Tourism Sector Revenue has a positive and significant influence on the Local Own-Source Revenue of Tabanan Regency. The Number of Tourist Visits, Hotel Occupancy Rates, and Tourism Sector Revenue simultaneously have a significant influence on the Local Own-Source Revenue of Tabanan Regency.